Utilization of phytoremediation capabilities of local flora integrated with constructed wetland for the development of graywater treatment and reuse system - Olalo, Kimberlyn Faith M.; Puso, Mark Ndsy L. (2020)
The Philippines is projected to face water shortage based on availability- and-demand with residential and commercial buildings responsible for over 70% of all fresh water potable water use. However, 50% of water used in residential and commercial buildings do not require a drinking water quality. The study aims to determine if the localized hybrid constructed wetland can be an alternative for the commercially available graywater treatment system. The research used experimental methods in investigating the phytoremediation capabilities of the pre-selected plant species, Duckweed (Lemna minor), Water hyacinth (Eichhornia crassipes), Indian shot (Canna Indica L.), Parakeet flower (Heliconia psi?ttacorum), Canna spp., and Taro (Colocasia esculenta). all set- ups. The first round of testing was intended to determine the higher performing plant species, which were Water hyacinth (Eichhornia crassipes), Indian shot (Canna Indica L.), and Taro (Colocasia esculenta). The second batch of tests were to determine which water classification, the hybrid set-up using the top performing plants, passed based on the DENR Administrative Order No.34, Series of 1990. The results and other factors were considered and analyzed to conclude that majority of the water parameters share a common factor which is temperature and the constructed wetland alone cannot reduce the number of the total coliforms. Thus, a few set-up revisions were applied such as providing a shading device and addition of a slow sand filter. The study concluded that the best water treatment performance was achieved by the hybrid constructed wetland with shading device and a slow sand filter which passed class C. In total, the study demonstrates the potential of constructed wetlands in treating graywater and can offer an alternative solution for water shortage.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020